The Legal Aspects Of Regulating The Submission Of Mining Business Permits In The Perspective Of The Mineral And Coal Mining Law - Andre Noverizky; Faidatul Hikmah (UIR Law Review, 2024)
This research explores the impacts of changes in the Mineral and Coal Mining Law, specifically from Law No. 4 of 2009 to Law No. 3 of 2020, on the mining sector in Indonesia. The background includes concerns about the potential centralization of authority, the removal of social responsibilities from mining companies, and perceived biases in environmental management favoring mining corporations. The methodology employed a normative approach, analyzing legislative changes and relevant literature to understand their implications. The findings indicate that the centralization of authority could pose challenges to the efficient and effective management of mining activities across Indonesia. The elimination of social responsibilities from mining companies may worsen the social and economic conditions of communities around mining areas. Environmental management dynamics, particularly those favoring mining companies, especially regarding reclamation plan requirements, could jeopardize environmental sustainability. In conclusion, changes in the Mineral and Coal Mining Law have significant implications for Indonesia's mining sector. Key challenges include the potential hindrance to efficient management due to centralization, the exacerbation of community welfare issues through the removal of social responsibilities, and environmental management dynamics that might threaten ecological sustainability. Continuous evaluation and adjustments within the regulatory framework are essential to strike a balance between encouraging investment, protecting communities, and preserving the environment in the Indonesian mining sector.